Analisis Hubungan Pengawasan dan Pelatihan K3 dengan Tindakan Tidak Aman (Unsafe Action) pada Pekerja di PT Prima Abadi Jaya Medan - Evfy Septriani Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Unsafe behavior in the workplace remains a major factor contributing to occupational accidents across industrial environments. Such behavior includes neglecting operational standards, using personal protective equipment (PPE) incorrectly, performing work hastily, or lacking sufficient alertness while carrying out tasks (Istih, 2017). Data reported by the Japan Industrial Safety and Health Association (JISHA) indicate that every year approximately 10,000 fatal incidents and more than two million workplace injuries occur in the United States, causing economic losses estimated at over 65 billion USD. In Indonesia, the Employment Social Security Agency (BPJS Ketenagakerjaan, 2022) recorded 35,291 occupational accident cases in 2020, which accounted for about 42.2% of all cases in West Java Province. These figures underscore the urgent need for effective and structured Occupational Safety and Health (OSH) implementation in various industrial sectors. This study investigates the relationship between workplace supervision and OSH training with unsafe work behavior among employees at PT. Prima Abadi Jaya Medan in 2023. The research applies a quantitative analytical design with a cross-sectional framework, observing conditions at a single point in time. The study population consisted of 120 workers, from which 51 respondents were chosen according to specified inclusion and exclusion criteria. Data were collected through a pre-tested structured questionnaire that met validity and reliability standards. Analytical techniques involved univariate and bivariate assessments using the Spearman rank correlation test, followed by linear regression through the enter method. The statistical analysis confirmed significant associations between supervision (p < 0.001) and OSH training (p < 0.005) with unsafe work behavior. The results indicate that both variables significantly influence unsafe actions, with supervision emerging as the most dominant factor in reducing unsafe practices at PT. Prima Abadi Jaya Medan.